2011
DOI: 10.1016/j.pnpbp.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously Hypertensive Rats (SHR) present deficits in prepulse inhibition of startle specifically reverted by clozapine

Abstract: Deficits in an operational measure of sensorimotor gating - the prepulse inhibition of startle (PPI) - are presented in psychiatric disorders such as schizophrenia, bipolar disorder, and attention deficit/hyperactivity disorder (ADHD). Some previous studies showed that the spontaneously hypertensive rats (SHR) present PPI deficit. Although SHR is suggested as an animal model to study ADHD, we have suggested that the behavioral phenotype of this strain mimics some aspects of schizophrenia. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 42 publications
5
47
0
Order By: Relevance
“…It has also been shown that NR3A knockout mice displayed increased prepulse inhibition [40], a measure of sensorimotor gating, which is a neurological process that occurs within the context of attentional processes. In a recent study, SHRs were also reported to present abnormalities in prepulse inhibition [41]. Whether changes in Grin3a brain gene expression in the SHR correlate with sensorimotor gating deficits or specifically, inattention in this rat strain should be clarified in future studies.…”
Section: Discussionmentioning
confidence: 91%
“…It has also been shown that NR3A knockout mice displayed increased prepulse inhibition [40], a measure of sensorimotor gating, which is a neurological process that occurs within the context of attentional processes. In a recent study, SHRs were also reported to present abnormalities in prepulse inhibition [41]. Whether changes in Grin3a brain gene expression in the SHR correlate with sensorimotor gating deficits or specifically, inattention in this rat strain should be clarified in future studies.…”
Section: Discussionmentioning
confidence: 91%
“…This was recently confirmed in spontaneously hypertensive rats (SHRs). These animals exhibit behavioral changes such as a basal disruption in PPI that have been associated with schizophrenia, since they are reversed by clozapine (Levin et al 2011). Similar to antipsychotic drugs, CBD also increases the PPI response in these (Levin et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These alterations are reversed specifically by antipsychotics and potentiated by psychostimulants or other pro-schizophrenia manipulations, showing predictive validity for the model Calzavara et al, 2009;Levin et al, 2011). In relation to the construct validity of the model, the SHR strain was initially developed from selecting rats from brother-sister mating of hypertensive Wistar to present a spontaneous hypertension phenotype (Okamoto and Aoki, 1963).…”
Section: Introductionmentioning
confidence: 99%